Feasibility and Usability of Immersive Virtual Reality Exergames for Patients With Parkinson’s Disease: A Pilot Study - Seung Hwan Lee; Seo Jung Yun; Minjung Kim; Byung-Mo Oh; Han Gil Seo (Annals of Rehabilitation Medicine, 2026)
Objective: To evaluate the feasibility, safety, and usability of a novel fully immersive virtual reality (VR) exergame, designed to incorporate cognitive-motor dual-task training for patients with Parkinson’s disease (PD).Methods: We developed a specialized fully immersive VR exergame program, featuring seven cognitive-motor dual-task games. Prior to the pilot study, we refined the system through two successive usability evaluations involving 17 and 15 rehabilitation experts, respectively, to optimize safety and interface design. Subsequently, four patients with idiopathic PD completed a 30-minute VR exergame session using the finalized system under therapist supervision. We assessed cybersickness using the Simulator Sickness Questionnaire (SSQ) and evaluated usability via the User Experience Questionnaire (UEQ) and a self-developed Custom Usability and Satisfaction Survey.Results: All participants completed the session without adverse events. Mean SSQ total scores decreased from 14.75±9.43 to 4.75±1.89 without statistical significance (p>0.05). UEQ demonstrated positive experiences, with Attractiveness (1.167), Efficiency (1.063), and Stimulation (1.500) exceeding benchmarks. Custom Usability and Satisfaction Survey scores for interest (6.00/7) and overall satisfaction (6.25/7) were high; however, physical comfort was rated relatively lower (4.25/7) due to the headset weight and safety harness.Conclusion: The developed fully immersive VR exergame system is feasible, safe, and engaging in patients with PD. Limitations include the small sample size and single-session design. Future research should focus on large-scale randomized controlled trials and hardware improvements to enhance physical comfort for long-term clinical application.